STATUS OF MILK AND MEAT HYGIENE IN SUDAN: REVIEW (Journal of Veterinary Medicine and Animal Production, 2022)
Protection against animal diseases and pests and against food safety threats and preventing their spread is one of the keys to fight hunger, malnutrition and poverty. However, the most reported outbreaks of food borne diseases are due to contamination of foods with zoonotic agents, often during primary production. The aim of this paper is to discuss the status of food safety research in Sudan with special reference to milk and meat hygiene. Zoonotic diseases such as brucellosis and tuberculosis can be transmitted by using unhygienic milk or milk products. This article reviews the above mentioned zoonotic diseases as well as the major pathogens of bovine mastitis which have a great impact on public health. The presence of antibiotic residues using the strainBacillus subtilis British type ATCC-bb33 as the test organism is also reviewed. An attempt was made in Sudan in order to apply Hazard Analysis Critical Control point (HACCP). Fore instance, poor building construction, poor water supply, poor farms hygiene as well as milkers and accumulation of dung and animal waste that induced insect spread are also reviewed.Hazard Analysis Critical Control point (HACCP) is the main issue of meat safety. Therefore, it has been reported that the isolated bacteria during assessment of meat hygiene practices in slaughter houses wereStaph. aureus, Staph. xylosus, Staph. lentus, Staph. auricularis, Staph. hominis, Bacillus cereus, Micrococcus spp and Escherichia.. Furthermore, these isolated bacteria were either non-pathogenic or opportunistic pathogens, and it is unlikely that these bacteria were from infected organs at postmortem examination, but from pitfalls in application of hygienic measures during skinning and handling of organs and carcasses. Moreover, the hygienic quality of mutton intended for export on basis of surface bacterial contamination which depends on critical contamination levels is also discussed.On the other hand, the paper reviews the pathological conditions, causing liver condemnations. Fore instance, parasitic infections particularly food borne parasites such as fascioliasis, cysticercosis have been recognized. The whole carcasses were mainly condemned due to tuberculosis, cysticercosis, jaundice, pyeamia and septicemia, while abscesses were the main causes of partial condemnations of carcasses. Based on all studies, it is important that milk and meat distribution chain should be monitored by health and Veterinary authorities to ensure safe food to consumers.Salmonella and other pathogens in poultry carcasses, livers, spleens, intestinal contents and related environments are also reviewed. The following isolates were recognized:Salmonella spp., Escherichia coli, Citrobacter spp., Klebsiella spp., Enterobacter hafni, Proteus spp., Acinetobacter spp., Edwardsiella tarda, Erwina herbicola, Yersinia spp., Serratia spp., Morganella spp., Hafnia alvei and Shigella spp. Overall, there is an urgent need for better monitoring and control food borne disease using new technologies.
Keywords: Food safety; Zoonotic diseases; Milk hygiene; Meat Hygiene; Sudan